Effect of salt stress on the biomass productivity and potential bioenergy feedstock of Graesiella emersonii KNUA204 isolated from Ulleungdo Island, South Korea - Do, Jeong-Mi; Yeo, Hee-Tae; Suh, Ho Seong; Yoon, Ho-Sung (Frontiers in Energy Research, 2023)
Microalgae are versatile, profitable, and promising sources of bioenergy and high-value products, having various applications in the biotechnology industry. Herein, G. emersonii KNUA204 was isolated from Ulleungdo Island, South Korea, and exposed to stressors, i.e., MgCl2 (75 and 150 mM) and NaCl (200 and 400 mM), to investigate improvement in its biomass productivity and feasibility of the application of biomass. Treatment with mild MgCl2 (75 mM) afforded the highest specific growth rate (μ = 0.13 d−1), dry cell weight (3 g L−1), and total carbohydrate content (29.87%). Although all salt treatments decreased chlorophyll and carotenoid contents, treatment with high NaCl concentration (400 mM) afforded the highest zeaxanthin content (0.3 mg g−1). The proximate and ultimate analyses of biomass following treatment with 150 mM MgCl2 revealed 93.85% volatile matter and 22.55 MJ kg−1 calorific value, respectively, indicating that Graesiella emersonii KNUA204 can be potentially used as bioenergy feedstock. The biodiesel quality was established based on the fatty acid methyl ester profiles, and MgCl2 treatment increased the cetane number more than the control. Therefore, the treatment of G. emersonii KNUA204 with MgCl2 during cultivation could provide a microalgae-based bioenergy feedstock with high productivity.